Die Station Nain im Winter von zugefrorener Bucht aus : [ca. 1901] - Schmitt, Christian, 1868-1933. (2001)
Black and white photograph of the mission station at Nain with a dog sled and team on the frozen bay, circa 1901. Black and white photograph of the mission station at Nain with a dog sled and team on the frozen bay, circa 1901.